Body image, physical activity and psychological health in older female cancer survivors. Issue 7 (September 2021) - Zhang, Xiaochen; Pennell, Michael L.; Bernardo, Brittany M.; Clark, Justin; Krok-Schoen, Jessica L.; Focht, Brian C.; Crane, Tracy E.; Shadyab, Aladdin H.; Paskett, Electra D.
Abstract: Objectives: To determine the association of physical activity and body image with psychological health outcomes and whether body image mediates the association of physical activity with psychological health among older female cancer survivors. Materials and Methods: Data from the Women's Health Initiative (WHI) Life and Longevity after Cancer (LILAC) Study were used. Surveys assessed body image (appearance, attractiveness, scars), moderate-strenuous physical activity (min/week), and psychological health (depression, anxiety, distress). A mediation analysis was conducted to estimate the percentage of the total effect of physical activity on psychological health mediated by body image concerns. Results: Among 4567 female cancer survivors aged 66–98 years, the average time since cancer diagnosis was 9.2 years. Approximately 50% reported no moderate-strenuous physical activity; 15% reported depressive symptoms, 6% reported anxiety, and 5% reported psychological distress; 3% had concerns with appearance, 20% had concerns with attractiveness, and 21% had concerns with scars. When unadjusted for body image concerns, every 30 min/week increase in physical activity was associated with lower risk of depressive symptoms (RR = 0.93, 95%CI: 0.90–0.96), anxiety (RR = 0.92, 95%CI: 0.87–0.97), and distress (RR = 0.92, 95%CI: 0.87–0.98). Body image concerns with appearance mediated 7%, 8.8%, and 14.5% of the association between physical activity and depressive symptoms, anxiety, and distress, respectively. Conclusion: Older female cancer survivors reported body image concerns, which were associated with both physical activity and psychological health. Our findings suggest that interventions designed to address body image concerns in older female cancer survivors could serve to improve the benefit of physical activity on psychological health.